Clinical features and related factors of freezing of gait in patients with Parkinson's disease - Fengting Zhang (Wiley, 2021)
Abstract Background Freezing of gait (FOG) is a disabling paroxysmal gait disorder that prevents starting or resuming walking, which seriously negatively affects patients’ quality of life (QOL). The diagnosis and treatment of FOG remain a huge medical challenge. The purpose of this study was to explore the clinical characteristics and related factors of FOG in patients with Parkinson's disease (PD). Methods The motor and nonmotor symptoms of a total number of 77 PD patients were evaluated. Patients with or without FOG were defined as a score ≥1 in the new freezing of gait questionnaire (NFOG‐Q). A comparative study between patients with and without FOG was conducted. Results In this investigation, the prevalence of FOG was 48%. The patients with FOG had longer disease duration, higher Hoehn‐Yahr stage (H‐Y stage), higher dose of dopaminergic agents, and higher nonmotor and motor symptom scores. A significant positive correlation was found between the NFOG‐Q score and the H‐Y stage, PIGD subscore, PDQ‐39, and the attention/memory in the nonmotor symptoms assessment scale (NMSS) subitem (r > 0.5, p < .05). The binary logistic regression analysis showed that the higher H‐Y stage, higher rigidity subscore and Unified Parkinson's Disease Rating Scale II (UPDRS II) score, and UPDRS III score were significantly correlated with the occurrence of FOG (p < .05). In the analysis of the frequency of FOG, the prevalence of FOG in H‐Y stage was higher in the middle and late stages, and the prevalence of FOG increased with the increase in PDQ‐39 scores. Conclusion The severity of FOG was significantly positively correlated with the H‐Y stage, PIGD subscore, PDQ‐39 score, and attention/memory score. Based on our findings, we conclude that the clinical characteristics of rigidity can be used as a potential predictor of FOG.